Usage of online platforms in education of mathematics in Transcarpathia at the beginning of quarantine - Papp Gabriella; Пап Габріелла (Ghent University, 2021)
Abstract. Distance learning and e-learning as concepts have been in our minds for a long time. In March 2020, they suddenly gained great importance due to the introduction of quarantine and were immediately put into practice. It had to be applied in the everyday lives of teachers and students with surprising speed. The goal of this research is to assess and demonstrate how teachers overcome the difficulties of mathematics education in distance learning. For this purpose, a month later after the beginning of distance education, I conducted a questionnaire survey among 20 teachers of mathematics in Transcarpathia with several different work experiences and who teach in several educational institutions. They were asked how education went on during quarantine, how they chose the platforms and methods needed to hold their lessons, what the checking and testing process was, what advantages and disadvantages they faced in distance learning.
https://cage.ugent.be/isaac2021/Abstracts_printing.pdf
Keywords: distance learning; e-learning; education; Transcarpathia; távoktatás; oktatás; Kárpátalja